Modeling Stress-Recovery Status Through Heart Rate Changes Along a Cycling Grand Tour - Barrero, Anna; Le Cunuder, Anne; Carrault, Guy; Carré, François; Schnell, Frédéric; Le Douairon Lahaye, Solène (Frontiers in Neuroscience, 2020)
Background: Heart rate (HR) and HR variability (HRV) indices are established tools to detect abnormal recovery status in athletes. A low HR and vagally-mediated HRV indices change between supine and standing position reflected a maladaptive training stress-recovery status. Objectives: Our study was focused on a female multistage cycling event. Its overall aim was two-fold: (1) quantify the correlation between (a) the change in HR and HRV indices during an active orthostatic test, and (b) and subjective/objective fatigue, physical load, and training level indicators; and (2) formulate a model predicting the stress-recovery status as indexed by Δ(RR) ̅ and ΔLnRMSSD (defined as the difference between standing and supine mean RR intervals and LnRMSSD respectively), based on subjective/objective fatigue indicators, physical load, and training levels. Methods: Ten female cyclists traveled the route of the 2017 Tour de France, comprising 21 stages of 200kms on average. From four days before the beginning of the event itself, and until one day after its completion, every morning, each cyclist was subjected to HR and HRV measurements, first at rest in supine position, and then in standing position. The correlation between HR and HRV indices and subjective/objective fatigue, physical load, and training level indicators was then computed. Finally, several multivariable linear models were tested to analyze the relationships between HR and HRV indices, fatigue, workload and training level indicators. Results: HR changes appeared as a reliable indicator of stress-recovery status. Fatigue, training level and Δ(RR) ̅ displayed a linear relationship. Among a large number of linear models tested, the best one to predict stress-recovery status was: Δ(RR) ̅= 1249.37 + 12.32 V ˙O2max + 0.36 km.week-1 - 8.83 HRmax - 5.8 RPE - 28.41 perceived fatigue with an adjusted R2=0.322. Conclusion: The proposed model can help to directly assess the adaptation status of an athlete from RR measurements, and thus to anticipate a decrease in performance due to fatigue, particularly during a multi-stage endurance event.